Aplicação do radiofármaco 68Ga-PSMA-11 PET/CT no estadiamento e diagnóstico de recidiva bioquímica de câncer de próstata - Diego, Regina Paula Soares (2023)
This study aimed to verify the performance of the application of positron emission computed tomography (PET/CT) using the radiopharmaceutical 68Ga-PSMA- HBED-CC (68Ga-PSMA-11) in the diagnosis of biochemical recurrence of prostate cancer through from the collection of data from examinations of eighty patients, with a mean age of 68.26 years, who received the radiopharmaceutical 68Ga-PSMA-11 intravenously with subsequent acquisition of images. Of the total number of patients admitted to the diagnostic imaging service, 70% had undergone prior radical prostatectomy (RP). The mean age of patients who presented a positive diagnosis was 68.85 years; for individuals with negative 68Ga-PSMA-11 PET/CT it was 64.91 years. Among the patients submitted to the PSMA PET-CT scan, 87.5% (70 patients) sought restaging related to the biochemical recurrence of the disease (the other 10 patients sought an initial diagnosis). The findings showed that in 85% of the cases (68 patients) there was abnormal accumulation of the radiotracer. Regarding the described findings, the results showed that 32.35% of the patients with positive 68Ga-PSMA-11 PET/CT showed abnormal concentration of the radiopharmaceutical in the prostate, 10.29% in the prostatic bed, 61.76% had compromised lymph nodes, 2.94% had disease in the seminal vesicles, 4.41% in the bladder and 26.47% of the patients had bone metastases. Serum PSA levels presented by patients who underwent PET-CT PSMA were below 1.0 ng/ml in 27.5% of cases; between 1.0 and 2.99 ng/ml in 28.75% of cases; between 3.0 and 6.99 ng/ml in 12.50% of cases; between 7.0 and 10.99 ng/ml in 12.50% of cases and greater than 11.0 ng/ml in 11.25% of cases. Most of the PET/CT images in the study indicated the presence of CP, despite the relatively low serum PSA level in most cases. Through this study, it was possible to conclude that the technique has advantages, demonstrating high sensitivity in the detection of small lesions, even under low serum levels of PSA, mainly with regard to lymph node and bone metastases. The results also reveal the popularization of the technique, suggesting an increase in its credibility in the medical community and showing considerable coverage of the procedure by health plans (1/3 of the procedures performed), demonstrating the gradual consolidation of the technique as a diagnostic method in the detection of cancer. prostate cancer, especially in the early stages of biochemical recurrence.